Statistics and ethics - Wyżnikiewicz, Bohdan (Annales. Etyka w Życiu Gospodarczym, 2019)
The article concerns ethical rules compiled by both public statistics and users of public statistics. Ethical rules in statistics are partly codified in the European Statistics Code of Practice published by Eurostat, the statistical bureau of the European Union. The implementation of this code is subject to periodical reviews. The second part of the paper deals with various manipulations of statistical data performed by their users. The thesis of the paper states that if non-ethical practices appear, either in public statistics or in manipulations by users, they are relatively quickly denounced. This thesis is supported by some empirical facts.